1998
DOI: 10.1161/01.atv.18.4.535
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Biochemical Alterations on Arterial Stiffness in Patients With End-stage Renal Disease

Abstract: Abstract-The incremental elastic modulus of the common carotid and radial arteries is increased in patients with end-stage renal disease (ESRD), independently of blood pressure, wall stress, and the presence of atherosclerotic alterations. Whether biochemical factors may be involved in the arterial changes and related to renal dysfunction remain largely ignored. To assess this question, we measured aortic (carotid-femoral), upper-limb (carotid-radial), and lower-limb (femoral-tibial) pulse wave velocity (PWV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
116
2
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(132 citation statements)
references
References 52 publications
9
116
2
5
Order By: Relevance
“…There is controversy over the effect of disorders of lipid metabolism on aortic compliance. In several cross-sectional studies, lipid profile was not a determinant of PWV, 5,6,9,29 whereas serum triglyceride correlated positively with ba-PWV in hemodialysis patients 30 and increments in ba-PWV. 28 Furthermore, intermediate-density lipoprotein cholesterol, which contains cholesterol and triglyceride, was an independent risk factor for arteriosclerosis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There is controversy over the effect of disorders of lipid metabolism on aortic compliance. In several cross-sectional studies, lipid profile was not a determinant of PWV, 5,6,9,29 whereas serum triglyceride correlated positively with ba-PWV in hemodialysis patients 30 and increments in ba-PWV. 28 Furthermore, intermediate-density lipoprotein cholesterol, which contains cholesterol and triglyceride, was an independent risk factor for arteriosclerosis.…”
Section: Discussionmentioning
confidence: 89%
“…Increased aortic stiffness, as assessed by pulse wave velocity (PWV), is an independent poor prognostic factor for cardiovascular disease and all-cause mortality in patients with ESRD. 3,4 Several studies showed that age, vascular calcification, 5,6 presence of diabetes mellitus 6 and vertebral bone mineral density 7 are determinants of aortic PWV in ESRD patients treated with hemodialysis (HD). Recently, we described that hemoglobin A1c was an independent contributor to aortic PWV not only in diabetic HD patients, but also in non-diabetic HD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest that pulse wave velocity (PWV) in patients with end-stage renal disease (ESRD) is elevated and predicts future cardiovascular disease and death (21)(22)(23). Furthermore, in one screened cohort, increased PWV was associated with low creatinine clearance, age, systolic blood pressure, proteinuria, fasting glucose, and cholesterol (12).…”
Section: Discussionmentioning
confidence: 99%
“…62 321; Biomérieux, Marcy-l'Etoile, France). Homocysteine level was estimated in plasma as previously described (Blacher et al, 1998).…”
Section: Biochemical Analysesmentioning
confidence: 99%